Dissolved Organic Matter Characteristics and Important Site Factors in a Subtropical Mountain Forest in Central China. Issue 1 (9th October 2019) - Wang, Min; Liao, Chang; Tian, Qiuxiang; Wang, Dongya; Wu, Yu; Tang, Yanan; Liu, Feng
Abstract: Dissolved organic matter is important in the vertical and lateral translocation of nutrients in forest ecosystems. However, little is known about the changes in dissolved organic matter concentration and chemical components in ecosystem sources in humid mountain forests. Here, we measured the concentration and chemical components of dissolved organic matter at throughfall, stemflow, litter leachate, runoff, and soil pore water (at depths of 10 cm, 30 cm, and 60 cm) in a subtropical humid mountain forest during two growing seasons. The concentration of dissolved organic carbon and dissolved nitrogen showed a clear monthly trend. The dissolved organic carbon concentration and the proportion of hydrophobic organic acid in the surficial water were higher than those in the soil pore water, and this difference was accompanied by a decrease in the hydrophobic organic acid concentration from the surficial water to the soil pore water. We also found that dissolved organic matter properties in surficial water were related to canopy cover, tree species, litter carbon content, and slope, whereas dissolved organic matter in soil pore water was associated with soil C, N, and P content and pH. In addition, the rainfall pattern is important to the dissolved organic matter concentration and partitioning within the seven sources. These findings showed that the dissolved organic carbon movement from surficial water into soil pore water is a significant component of carbon cycling in forest ecosystems, and this is important in estimating the carbon budget in forest ecosystems.